Direct measurement of the position accuracy for low energy X-ray photons with a pnCCD. (6th February 2017) - Ihle, S.; Holl, P.; Kalok, D.; Hartmann, R.; Ryll, H.; Steigenhöfer, D.; Strüder, L.
Abstract: We undertook a comparative study on optimizing the position accuracy of pnCCDs for single X-ray photon measurements. Various methods were analyzed by Monte Carlo simulations and related to experimental data obtained with a focused X-ray beam. Even with low energy photons of 1320 eV, a position accuracy much smaller than the actual pixel size of 48 μm × 48 μm can be achieved. This is possible since signal charges from a single photon interaction spread into more than one pixel, allowing a reconstruction of the original point of interaction. We found that a) making a decision on which pixels to use for the reconstruction and b) choosing a centroiding algorithm for carrying out the reconstruction were particularly crucial. For a) we introduce a new and superior method using a two step analysis with an adaptive pattern. It is compared to using a threshold or a fixed pattern. For b) we present a Center-of-Gravity method with a Gaussian correction taking into account the shape of the signal charge cloud. Both methods are also optimized for fast execution by implementing lookup tables rather than time consuming calculations. Our results show that with the appropriate analysis an uncertainty of the position measurement of better than 3.0 μm rms for 1320 eV photons is possible.